Code-switching as a pedagogical practice for senior phase teachers teaching content subjects in OR-Tambo district - Marcia M. Seabela; Thobeka Ncanywa (AOSIS, 2024)
Background: The notion that teaching content subjects in schools utilising code-switching as a pedagogical approach contributes positively to academic achievements is well documented. Aim: This article demonstrates the effectiveness of code-switching as a pedagogical practice for senior-phase teachers teaching content subjects in some selected schools of the OR-Tambo education district. Setting: The study was conducted in three semi-rural schools in the Eastern Cape province. Methods: The study utilised a mixed-method research approach in three public schools. Participants were purposefully selected. Thematic content analysis was used to interpret the results. Results: The findings of this study indicated that teachers' frequent use of code-switching during the senior phase teaching of the English language is a norm in a classroom. At the same time, learners were frustrated to learn the content subjects in English. Moreover, poor learner academic background affects their academic performance in the content subjects. The study reveals a notable lack of pedagogic support for teachers from officials in the Department of Education as well as a sizable component of the school administration team. Conclusion: The use of code-switching is a useful tool to improve the effectiveness of teaching and learning in senior-phase lessons. Contribution: The study recommends that teachers and learners be encouraged to use code-switching, especially when dealing with difficult material to be taught in English. The study recommends that the Department of Education conduct extensive workshops on professional growth. This all-encompassing strategy might seek to strengthen the senior phase classroom, creating a lively and encouraging atmosphere for teachers and learners alike.